ANALISIS STRATEGI PEMASARAN DAN PENERAPAN SKEMA PEMBIAYAAN PADA BSI OTO : STUDI PADA BSI KCP KEDIRI BANDAR - Istiyadah, Narulita Al Kholifina (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the marketing strategies and financing scheme implementation of the BSI OTO product at BSI KCP Kediri Bandar. As a Sharia-based automotive financing product, BSI OTO applies the murabahah contract combined with a joint financing scheme in collaboration with Mandiri Utama Finance (MUF). This research employs a descriptive qualitative method through interviews, observations, and document analysis. The findings reveal that BSI OTO’s marketing strategies include institutional presentations, brochure distribution, partnerships with vehicle showrooms, and both internal and external promotional events. The murabahah contract is applied transparently using a declining annuity scheme, although further customer education on its mechanism is still needed. Despite its potential, data indicate a decline in financing since March 2025 due to competition and economic conditions. Therefore, revising marketing strategies, strengthening Sharia financial literacy, and enhancing synergy with partners are crucial efforts to improve the competitiveness of BSI OTO in the future.